PEMAHAMAN SENSITIVITAS GENDER PEGAWAI KANTOR URUSAN AGAMA TERHADAP PERNIKAHAN USIA ANAK - Gunawan, Indra; Antasari, Rina; Azkia, Zuraidah (Universitas Islam Negeri Raden Fatah Palembang, 2024)
Child marriage is still prevalent in Indonesian society, one of which occurs in Ilir Timur II District, as data found that there are still marriages that are registered but do not meet the age requirements for marriage determined by law. The purpose of this research is to understand the gender sensitivity of Religious Affairs Office employees in Ilir Timur II District Palembang City towards child marriage and understand the form of gender sensitivity of Religious Affairs Office (KUA) employees in Ilir Timur II District in minimizing the occurrence of child marriage. The method used in this research is qualitative research method, type of field research with normative-empirical approach. The results of this study state that the understanding of gender sensitivity on the part of employees of the Religious Affairs Office of the Ilir Timur II District emphasizes the importance of a deep understanding of gender roles and identities to prevent injustice in domestic life. In addition, the emphasis on Law No. 16 of 2019 which raises the minimum age of marriage for women to 19 years is also part of the understanding of gender sensitivity. The form of gender sensitivity of employees of the Religious Affairs Office (KUA) of Ilir Timur II District in minimizing the occurrence of marriage at the age of a child is by examining the marriage file in detail and socializing through lectures or counseling to increase public understanding and awareness in order to meet the requirements of sufficient age before marriage.